PEMBUATAN DEKORASI RUMAH PENGANTIN DI DWIKA DEKORASI DESA SELAT, BULELENG, BALI - Putu Yudik Suarmawan; Gede Eka Harsanan Koriawan; I Nyoman Rediasa (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
This article contains part of the thesis entitled "Making Bridal Home Decorations in Dwika Decorating Selat Village, Buleleng Bali" qualitative research with the objectives: (1) To describe the existence of bridal house decorations in Dwika Decorating Selat Village, Buleleng, Bali. (2) To find out the materials and tools used in making decorations at the gate of the bride's house (3) To understand and know the process of making decorations for the gate of the bridal house and (4) To find out the designs and motifs used in decorating the gates of the bridal house in Dwika Decorating Selat Village, Buleleng, Bali. The data was obtained through the stages of observation and interviews with the business owner of Deika Decor then the data was processed using the Sparadley model (1980) by analyzing the domain and taxonomy. , Bali . (2) the materials used are teak wood, coconut leaves (young, old, and dry), rope (bamboo rope, macrame rope), paint, wire, and nails, while for scissors, saws, knives (large and small) , pliers, tape measure, hammer, kacip (shooter blade and ordinary kacip), and brush. (3) Making decorations for the gate of the bride's house, namely the ordering process, making the frame, making hisan, and installing it. (4) designs and decorations are of two types, namely traditional and modern designs. Keywords: Decoration, Bridal House, Straits Village.